EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN NANAS DI DAS MIKRO SUPITURUNG KECAMATAN PLOSOKLATEN KABUPATEN KEDIRI JAWA TIMUR - Sarah Nur Shabrina; Mochtar Lutfi Rayes; Christanti Agustina (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Fruit plants in Kediri Regency are classified as having good economic potential, one of which is pineapple. Pineapple plants in Kediri Regency have differences in productivity in each sub-district. The results of interviews with local farmers indicated that the Supiturung Micro Watersheds in Plosoklaten District had low pineapple productivity and were not yet optimal. Therefore, this study aimed to determine the factors causing differences and less optimal productivity of pineapples in the Supiturung Micro Watersheds and analyze the land suitability assessment of pineapple plants in the region. This study used a survey method with a physiographic approach to 10 Land Map Units (LMU) and determined 20 observation points as representatives. Data analysis was performed through correlation and multiple regression tests with the stepwise method to determine the land characteristics that most significantly affected pineapple productivity. Modification of the suitability class and modification of the criteria was carried out utilizing boundary line analysis, with class boundaries according to FAO (1976), namely class S1 (80-100%), S2 (60-80%), S3 (40-60%), and N (<40%) of the potential productivity. The land suitability evaluation results of pineapple plants in the Supiturung Micro Watersheds were included in land suitability classes S2, S3, and N. Based on the stepwise method analysis, the texture is a significant characteristic affecting the productivity of pineapples (p <0.05) with a correlation coefficient value of 0.838. The modification of land suitability criteria with boundary line analysis resulted in changes in one land characteristic, namely soil texture S2, S3, and N. Initially, the rough class included in the N class was changed to S2 level along with the slightly rough level.